Othello - Shakespeare, William, 1564-1616.; Holste, Gayle (Hauppauge, NY : Barron's Educational Series, 2002)
Presents the original text of Shakespeare's play side by side with a modern version. Includes a section with discussion questions and quizzes for students.
"Modern English version side-by-side with full original text."
Keywords: Othello -- (Fictitious character from Shakespeare) -- Drama; Shakespeare, William, -- 1564-1616.; Shakespeare, William, -- 1564-1616 -- Criticism and interpretation; Jealousy -- Drama; Muslims -- Drama; Plays; Venice (Italy) -- Drama